2011
DOI: 10.1159/000323774
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Hyperprolactinemia on Carrageenan-Induced Inflammatory Paw Edema in Rats

Abstract: Objectives: The effects of short-term 5-day and long-term 30-day hyperprolactinemia induced by domperidone (1.7 mg/kg/day, s.c.) or ectopic pituitary graft on the acute inflammatory response induced by carrageenan were evaluated in male rats. Both models of hyperprolactinemia effectively increased serum prolactin (PRL) levels. Methods: The volume in milliliters of inflammatory edema was measured by plethysmography 1, 2, 3, 4, 6, 8 and 24 h after carrageenan injection. The areas under the inflammatory time-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 106 publications
0
2
0
4
Order By: Relevance
“…The data presented here mostly cover short-term actions (Ͻ5 days) of PRL and PRL-R and demonstrate that the disruption of PRL and PRL-R significantly decreases inflammatory hyperalgesia at 1-24 h post-CFA. Interestingly, shortterm hyperprolactinemia increased inflammatory edema in male animals, whereas long-term 30-day hyperprolactinemia had anti-inflammatory effects (1,55). Fifth, it has been shown that PRL produces antihyperalgesic effects in lactating females (60,63).…”
Section: Discussionmentioning
confidence: 98%
“…The data presented here mostly cover short-term actions (Ͻ5 days) of PRL and PRL-R and demonstrate that the disruption of PRL and PRL-R significantly decreases inflammatory hyperalgesia at 1-24 h post-CFA. Interestingly, shortterm hyperprolactinemia increased inflammatory edema in male animals, whereas long-term 30-day hyperprolactinemia had anti-inflammatory effects (1,55). Fifth, it has been shown that PRL produces antihyperalgesic effects in lactating females (60,63).…”
Section: Discussionmentioning
confidence: 98%
“…Domperidone was administered at a dose of 1.7 mg × kg– – (i.p.) 3 times per day (6: 30 a.m., 2: 00 p.m., and 9: 00 p.m., therefore a total of 5.1 mg × kg –1 per day) for 5 consecutive days from the 10th to 14th day after OVA immunization [13, 37, 38]. This treatment protocol has effectively produced stable hyperprolactinemia for more than 30 days [13, 39].…”
Section: Methodsmentioning
confidence: 99%
“…É amplamente conhecido que a administração de domperidona por sua propriedade de bloquear os receptores D2 de dopamina, particularmente aqueles do sistema dopaminérgico tuberoinfundibular, induz hiperprolactinemia (BAILEY; HERBERT, 1982;BRIDGES, 1992;NASELLO et al, 1997;CRUZ-CASALLAS et al, 1999;OCHOA-AMAYA et al, 2011. Os resultados do primeiro experimento da tese confirmam esse efeito da domperidona e são consistentes com achados anteriores do nosso laboratório (BAILEY;HERBERT, 1982;CHAMPION, 1988;BRIDGES, 1992;NASELLO et al, 1997;CRUZ-CASALLAS et al, 1999;OCHOA-AMAYA et al, 2010, 2011.…”
Section: Discussionunclassified
“…Além disso, níveis elevados de citocinas pró-inflamatórias Th2 como IL-5 (ZHOU et al, 2015), IL6 (WONG et al, 2001 -FREITAS et al, 2007-FREITAS et al, , 2008-FREITAS et al, , 2011 A prolactina promove respostas imunes pró-inflamatórias via NFκB e fator regulatório do interferon 1 (IRF-1), que é um fator de transcrição multifuncional e um importante regulador da diferenciação e maduração dos linfócitos T e B (MÉNDEZ-HERNÁNDEZ; CARIÑO; DÍAZ, 2005). Esses fatores citados são conhecidos por induzir aumento do TNFα considerado mediador essencial de inflamação (OCHOA-AMAYA et al, 2011). O TNFα é uma citocina pro-inflamatória (BERRY et al, 2007) com uma extensa organização de atividades imuno-modulatórias (RUSSO; POLOSA, 2005;OYOSHI et al, 2008), sua função precisa na patogênese da asma ainda não está muito clara (OYOSHI et al, 2008 (NAGATA et al, 1999).…”
Section: Discussionunclassified
See 1 more Smart Citation